Tuning the decay time of plastic scintillators. (June 2019) - Hamel, Matthieu; Soumaré, Malik; Burešová, Hana; Bertrand, Guillaume H.V.
Abstract: In the field of nuclear physics, plastic scintillators are popular and efficient radiation detectors thanks to the following properties: they can be prepared in large volumes, are cheap and various configurations can be afforded to the material. However, peculiar applications might require plastic scintillator with unusual scintillation decay times, such as laser beam positioning or detectors stacking. In the case of the scintillation decay time, commercial suppliers do not propose many choices, as only the range 0.7–10 ns is usually covered, along with a longer decay time – 285 ns – material. Herein we propose a new concept and associated formulations where the scintillation decay time can be finely chosen and tuned in a range starting at 2.5 ns and finishing around 90 ns. These materials are presented, synthesized and characterized. Highlights: New plastic scintillators are presented, showing an unusual decay time. A combination of two different primary fluorophores allows tuning the photoluminescence decay time of the material. The plastic scintillators are fully characterized.